ALTERATIONS OF LOCAL ADAPTIVE IMMUNITY IN POLYPOUS RHINOSINUSITIS - Khodjanov Shokhimardon Khodjanovich; Djuraev Jamolbek Abdukaharovich; Soatov Ilyasjon Olim oglu; Rasulova Nasiba Shavkatovna; Mardonov Khurshed Azamkul ugli (Web of Journals Publishing, 2024)
The etiology and pathogenesis of PRS remain unclear. Many works in this direction did not change the situation. However, ideas about the pathogenesis of PRS have recently undergone significant changes, primarily due to advances in the field of clinical immunology of ENT diseases. In all theoretical views on the genesis of nasal polyps, the involvement of the immune system, especially the immune status of the nasal mucosa, plays a leading role.
Keywords: Chronic polyposis rhinosinusitis, sinus surgery, endoscopy, FESS operations.